Developing Adolescents' Morals in Realizing the Quranic Generation: Pembinaan Akhlak Remaja dalam Mewujudkan Generasi Qurani - Dianto, Dianto; Amini, Nur Rahmah; Daulay, Mahmud Yunus (Universitas Muhammadiyah Sidoarjo, 2024)
Moral development is the first focus of attention in Islam. This is in accordance with one of the missions of the Prophet Muhammad SAW. to perfect noble morals. That basically humans are born in a state of fitrah which in this case includes moral fitrah, which is then perfected through the apostolic mission of the Prophet Muhammad SAW. in the form of teachings brought by the Apostle.Coaching is an educational effort both formal and non-formal which is carried out consciously, planned, directed, organized and responsible in order to introduce, grow, develop a balanced, intact and harmonious personality base. Knowledge and skills in accordance with their own talents, desires and initiatives, add, improve and develop towards the achievement of dignity, quality and optimal human abilities and independent individuals.This research is a qualitative research by taking several activities ranging from observation, interviews, and documentation. The results of this study show that first, moral guidance for adolescents is very important to be applied by all educators. Second, the supporting factor is good cooperation between educators and parents. While the inhibiting factor is the association of teenagers with the outside environment which sometimes brings negative directions.